Respuesta :
Subtract
2y
from both sides of the equation.
3x=−2y+
39Divide each term by 3 and simplify.
Divide each term in 3x=−2y+393x=-2y+39by 33.
3x3=−2y3+3933x3=-2y3+393
Reduce the expression by cancelling the common factors.
Tap for more steps...
x=−2y3+393x=-2y3+393
Divide 3939 by 33.
x=−2y3+13
2y
from both sides of the equation.
3x=−2y+
39Divide each term by 3 and simplify.
Divide each term in 3x=−2y+393x=-2y+39by 33.
3x3=−2y3+3933x3=-2y3+393
Reduce the expression by cancelling the common factors.
Tap for more steps...
x=−2y3+393x=-2y3+393
Divide 3939 by 33.
x=−2y3+13
Answer:
The Coordinates are (5, 12)
Step-by-step explanation:
Edge 2021